PENATAAN DAN PEMBINAAN PEDAGANG KAKI LIMA DALAM PERSPEKTIF KOMUNIKASI PEMBANGUNAN DI SURAKARTA - Muhammad Fajar Pramono (Kopertais Wilayah X Jawa Tengah, 2015)
AbstractAlways talking about controlling street vendors ( PKL) like tangle and even there is always resistance. Such events occur in almost all regions in Indonesia. They differ in Surakarta voluntarily move to a location that has been prepared by the Government. The purpose of this study is expected to evaluate the response of vendors to process structuring and development of street vendors conducted by the City Government of Surakarta, especially during Joko Widodo-Rudy (2005-2012), so that it can be done peacefully. This study uses a quantitative approach using surveyexplanatory. To analyze the factors of interpersonal communication and democratic leadership style factors Surakarta City Government on the effectiveness of communication by using multipleregression analysis. Sample as many as 243 respondents using systematic random sampling. First results showed that the success of the process of structuring and development of street vendors in Surakarta in PKL assessment not only in the context of the process, but also in the sense of the results. Second, the results showed a factor of interpersonal communication and democratic leadership style factors jointly affect significantly on the effectiveness of Surakarta City Government communication in the process of structuring and development of street vendors. However, if both factors are seen individually that research shows that the democratic leadership style factors Surakarta City Government contributes more than a factor of interpersonal communication on the effectiveness of Surakarta City Government communication. Third, the results showed that the effectiveness of communication with Surakarta City Government Development productivity showed a positive relationship. Keywords: Development Communication, Management and Development of street vendors and governmentSurakarta City